Pengaruh Powerpoint Interaktif Terhadap Peningkatkan Hasil Belajar IPA Siswa UPTD SD Negeri 70 Parepare - Ila Israwaty; Kamaruddin Hasan; Indriani (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this study is to evaluate the improvement of science learning achievement among fifth-grade students of UPTD SD Negeri 70 Parepare who utilize interactive PowerPoint-based learning media, as well as to assess the impact of that learning media on science learning outcomes. The method employed is a quantitative approach with an experimental research design using One-Group Pretest-Posttest in the form of Pre-experimental design. The research sample was taken comprehensively. Data were collected through multiple-choice tests and analyzed using descriptive and inferential analysis techniques. Descriptive results indicate an increase in the average score from 34.57 in the pretest to 79.32 in the posttest. Inferential analysis reveals a significant improvement in science learning outcomes following the application of interactive PowerPoint learning media. The hypothesis testing using the Paired Sample T-test rejects H0 and accepts H1, confirming that the use of interactive Powerpoint learning media positively influences the science learning outcomes of fifth-grade students at UPTD SD Negeri 70 Parepare.